Training on water acidity level (pH) measurement for disease prevention in Sukmajaya Subdistrict, Depok City - Dewi Syavitri; Suliestyah Suliestyah; Yarra Sutadiwiria; Moehammad Ali Jambak; Rendy Rendy; Imam Setiaji Ronoatmojo; Firman Herdiansyah; Suryo Prakoso; Budi Wijaya; Lalita ‘Afin; Suci Maharani (Community Empowerment, 2025)
This community service activity aims to educate the public about the quality of groundwater consumed. The training was conducted at the Sukmajaya Urban Village Office, Sukmajaya District, Depok City, and was attended by 17 participants consisting of village officials and residents. This training utilized pH indicator paper. Based on the evaluation results, public understanding of the clean water quality standards issued by the Ministry of Health of the Republic of Indonesia has increased, with 90% of participants recognizing that normal pH levels are a requirement for consumable clean water, 90% of participants understanding the appropriate pH levels for drinking water, and 100% of participants being aware of the Minister of Health Regulation on drinking water standards and sanitation regulations.